1993
DOI: 10.1093/hmg/2.12.2055
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin expression improves myofiber survival in mdx muscle following intramuscular plasmid DNA injection

Abstract: Expression of Becker-like and full-length human dystrophins was stable for at least 6 months in mdx mouse muscle following intramuscular plasmid DNA injection. Intramuscular injection of a single plasmid DNA encoding both luciferase and dystrophin resulted in stable luciferase expression for at least 2 months in mdx muscle, whereas injection of plasmid DNA encoding only luciferase did not result in stable luciferase expression. These results suggest that expression of either full-length or Becker-like dystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…For example, nNOS localization to the sarcolemma requires elements of the rod domain that are missing in the recombinant minidystrophin. 30,31 Plasmid DNA is able to accommodate the 14 kb full-length cDNA and has been used to deliver the dystrophin gene into the muscles of mdx mice, 18,32,33 although with a low efficiency. Recently, the use of electroporation to introduce plasmids into muscle has increased gene transfer efficiency, 25 including delivery of full-length dystrophin into the skeletal muscle of mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nNOS localization to the sarcolemma requires elements of the rod domain that are missing in the recombinant minidystrophin. 30,31 Plasmid DNA is able to accommodate the 14 kb full-length cDNA and has been used to deliver the dystrophin gene into the muscles of mdx mice, 18,32,33 although with a low efficiency. Recently, the use of electroporation to introduce plasmids into muscle has increased gene transfer efficiency, 25 including delivery of full-length dystrophin into the skeletal muscle of mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…24,45 Various studies reported an anti-dystrophin immune response following intramuscular injections of vectors, especially viruses. 8,27,42 This could be explained at least in part by the expression in mice of a human dystrophin protein. This foreign antigen-specific response is supported by our present study and further sustantiated by our observation that there was no decrease of the amount of revertant fibers following human dystrophin plasmid administration.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal and cardiac muscles have the ability to take up and express naked plasmid DNA injected into the extracellular space in vivo, 26 and experiments performed in mdx mice have shown uptake and expression of the full-length dystrophin cDNA. 8,27 Prolonged expression of non-or poorly immunogenic foreign transgene was demonstrated using intramuscular (i.m.) administration of naked DNA, with the example of a 19-month expression of a luciferase reporter gene construct introduced directly into mouse muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike viral vectors, repeat deliveries of pDNA for chronic diseases are possible because pDNA does not induce an immune response toward the vector ( Jiao et al, 1992;Le et al, 2000;Zhang et al, 2001;Hagstrom et al, 2004;Romero et al, 2004). The pDNA delivered to skeletal muscles of rodents or primates is retained in muscle fibers and expresses the encoded gene product for many months, if not years (Wolff et al, 1992;Danko et al, 1993Danko et al, , 1997Zhang et al, 2004Zhang et al, , 2010Sebestyen et al, 2007). Long-term expression of foreign genes can be obtained from naked pDNA without chromosomal integration if the target cell is postmitotic (e.g., muscle fibers) or slowly mitotic (e.g., hepatocytes) and if there is no immune response to the expressed gene (Wolff et al, 1992;Miao et al, 2000;Herweijer et al, 2001;Zhang et al, 2001;Wooddell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Initially pDNA was delivered to muscles by intramuscular injection (Wolff et al, 1992;Danko et al, 1993Danko et al, , 1997). Vascular delivery procedures were then developed to deliver pDNA to skeletal muscles of a whole limb by injection into an artery (Budker et al, 1998;Zhang et al, 2001Zhang et al, , 2004Danialou et al, 2005) or a vein (Hagstrom et al, 2004;Kamimura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%